Strategi Membangun Brand Image Guna Peningkatan Daya Saing di Sekolah SMA Yadika 6 - Imron Permana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze strategies for building brand image to enhance the competitiveness of educational institutions at SMA Yadika 6. The research is motivated by the increasingly competitive educational environment, particularly in urban areas, which requires schools not only to improve educational quality but also to establish a strong and credible institutional image. Brand image is considered a strategic factor that influences public trust and attracts prospective students. This research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews, observations, and documentation. Research informants included the school principal, education supervisors, quality assurance teams, student affairs coordinators, admissions committee heads, students, alumni, parents, and parents from competing schools. Data analysis was conducted using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the brand image of SMA Yadika 6 is developed through strengthening the quality of educational services, fostering academic and non-academic achievements, reinforcing school culture, and utilizing digital media as communication and promotional tools. Strategies to build and maintain brand image are implemented in an integrated manner through improving human resource quality, managing flagship programs, and strengthening relationships with parents and alumni. The implications of these strategies are reflected in increased public trust, positive perceptions of the school, and enhanced institutional competitiveness amid inter-school competition.